Civic Engagements: The Citizenship Practices of Indian and Vietnamese Immigrants - Brettell, Caroline; Reed-Danahay, Deborah (Stanford University Press, 2011)
For refugees and immigrants in the United States, expressions of citizenship and belonging emerge not only during the naturalization process but also during more informal, everyday activities in the community. Based on research in the Dallas–Arlington–Fort Worth area of Texas, this book examines the sociocultural spaces in which Vietnamese and Indian immigrants are engaging with the wider civic sphere. As Civic Engagements reveals, religious and ethnic organizations provide arenas in which immigrants develop their own ways of being and becoming "American." Skills honed at a meeting, festival, or banquet have resounding implications for the future political potential of these immigrant populations, both locally and nationally. Employing Lave and Wenger's concept of "communities of practice" as a framework, this book emphasizes the variety of processes by which new citizens acquire the civic and leadership skills that help them to move from peripheral positions to more central roles in American society.